Ion beam processing of DNA origami nanostructures - Sala, Leo; Zerolová, Agnes; Vizcaino, Violaine; Mery, Alain; Domaracka, Alicja; Rothard, Hermann; Boduch, Philippe; Pinkas, Dominik; Kocišek, Jaroslav (Beilstein Journal of Nanotechnology, 2024)
DNA origami nanostructures are emerging as a bottom-up nanopatterning approach. Direct combination of this approach with top-down nanotechnology, such as ion beams, has not been considered because of the soft nature of the DNA material. Here we demonstrate that the shape of 2D DNA origami nanostructures deposited on Si substrates is well preserved upon irradiation by ion beams, modeling ion implantation, lithography, and sputtering conditions. Structural changes in 2D DNA origami nanostructures deposited on Si are analyzed using AFM imaging. The observed effects on DNA origami include structure height decrease or increase upon fast heavy ion irradiation in vacuum and in air, respectively. Slow- and medium-energy heavy ion irradiation results in the cutting of the nanostructures or crater formation with ion-induced damage in the 10 nm range around the primary ion track. In all these cases, the designed shape of the 2D origami nanostructure remains unperturbed. Present stability and nature of damages on DNA origami nanostructures enable fusion of DNA origami advantages such as shape and positioning control into novel ion beam nanofabrication approaches.
Keywords: DNA nanotechnology; DNA origami; FIB; heavy ions